CHILD syndrome: successful treatment of skin lesions with topical lovastatin and cholesterol lotion - Karina Romero Sandoval; Maria Cecília Rivitti Machado; Zilda Najjar Prado de Oliveira; Marcello Menta Simonsen Nico (Sociedade Brasileira de Dermatologia, 2019)
Abstract: CHILD syndrome (Congenital Hemidysplasia, Ichthyosiform erythroderma, Limb Defects) is a rare X-linked dominant disease. The authors report a 2-month-old patient presenting with typical features of CHILD syndrome that was treated with a topical solution containing cholesterol and lovastatin, with complete clearance of her CHILD nevus. The changes in skin lipid metabolism that explain the CHILD ichthyosiform nevus and their correction through topical application of cholesterol and lovastatin are discussed.